Iraq and Turkey - South-South Knowledge Exchange on Social Safety Nets - Alkhoja, Ghassan; Nsour, Surat; Dawani, Zaina (World Bank, Washington, DC, 2012)
South-South knowledge exchanges present an excellent model for knowledge sharing between countries, organizations, and individuals. They create opportunities for peer-to-peer learning and dialogue among policy makers, practitioners, and the broader community of Civil Society Organization (CSO), academics, etc. To this end an Iraqi delegation from the Ministry of Labor and Social Affairs (MOLSA) visited the Social Assistance and Solidarity Fund (SASF) in Turkey in January 2012 to learn from the Turkish experience in developing social assistance programs and social safety nets. The World Bank's first annual report on knowledge identified three knowledge roles for the Bank: as producer, customizer, and connector. This quick note will focus on the role of the Bank as a connector and underlines the importance of this role. It also highlights the momentum that South-South knowledge exchanges are gaining and its role as an effective catalyst for capacity development.